Tanggung Jawab Keluarga Sebagai Pusat Pendidikan Rohani: Analisis Ulangan 6:4-9 - Andri Harvijanto (Sekolah Tinggi Teologi Injili Indonesia Palu, 2024)
The book of Deuteronomy is the story of the history of the Israelites as God's chosen people, who live their lives only because of God's leadership and power. Living by loving God with all your heart, strength and mind is the only way to experience God's power and love. The book's actual name in Hebrew is summarized in the opening line that reads